Nonalcoholic Fatty Liver Disease in Chronic Hepatitis B and C Patients from Western Amazon - A. C. M. Nascimento; D. R. Maia; S. M. Neto; E. M. Lima; M. Twycross; R. F. Baquette; C. M. O. Lobato (International Journal of Hepatology)
Nonalcoholic fatty liver disease (NAFLD) includes a wide spectrum of histological conditions, extending from simple steatosis to end-stage liver failure. The aim of this study was to examine the prevalence of NAFLD and its associations in chronic hepatitis B and C patients. Methods. We included all patients diagnosed with chronic hepatitis B and C who underwent a liver biopsy between January 2010 and October 2011 (n = 104). Parameters studied included hepatitis type, anthropometric data, histologic, hepatic, metabolic and lipid assessments, presence of hypertension and viral load. Results. Hepatitis B was presented in 28.8% (n = 30) of patients, while hepatitis C was presented in 71.2% (n = 74). In addition, hepatic steatosis was present in 25% (n = 26) of the patients. Steatosis was frequently found in hepatitis C patients (31.1%; 25% n = 23), but infrequently in hepatitis B patients (10%; n = 3) (P = 0.024). It was also found that steatosis was frequently present in hepatitis C patients with intense fibrosis (52.94%) (P = 0.025). Discussion. Our results suggest that steatosis is a common feature in patients with viral chronic hepatitis, and that it plays a different role in each type of hepatitis.